Anti-infective dyes in the time of COVID. (December 2021) - Wainwright, Mark
Abstract: The phenomenal global upheaval caused by SARS-CoV-2 has produced amazing responses from science and healthcare, particularly in the rapid realisation and production of vaccines. However, until early 2020 global infection control research was highly focused on rapidly increasing rates of conventional antimicrobial resistance (AMR) and the supply of drugs to counter this. Antimicrobial dyes have been suggested by various authors for inclusion in this effort, usually with little return from responsible authorities, and normally on the basis of post-treatment staining or potential toxicity, but this does not deny the fact that such dyes, particularly with photoactivation, are the only class of agents with pan-microbial activity – i.e. against each of bacteria, viruses, fungi and protozoa – regardless of the organism's drug resistance status. Conventional antibacterials, antivirals etc. usually demonstrate activity against one particular section of pathogens only, and disinfectants such as chlorhexidine or benzalkonium salts are too toxic for internal use. This perspective reflects both the background utility of antimicrobial dyes and ways forward for their inclusion in 21st Century infection control protocols. Highlights: Locally applied dyes offer effective disinfection. Photodynamic action allows much increased antimicrobial action. Photoantimicrobials can be used for blood product disinfection. Photodecolonisation can be used to counteract infection transmission, e.g. of COVID.